A recursive construction of the regular exceptional graphs with least eigenvalue –2 - Barbedo, Inês (2014)
In spectral graph theory a graph with least eigenvalue −2 is exceptional if it is connected, has least eigenvalue greater than or equal to −2, and it is not a generalized line graph. A (κ,τ)-regular set S of a graph is a vertex subset, inducing a κ-regular subgraph such that every vertex not in S has τ neighbors in S. We present a recursive construction of all regular exceptional graphs as successive extensions by regular sets.